Modul Struktur dan Perkembangan Organ Reproduktif Tumbuhan Berbasis Ethno-STEM - Santika, Dwi; Ami, Mucharommah Sartika (JoEMS (Journal of Education and Management Studies), 2023)
This study aims to describe the feasibility of the structural and developmental modules of ethno-STEM based plant reproductive organs according to expert validation. The research method used was Borg & Gall development research which consisted of the first five stages, namely Research and information collection, Planning, Developing preliminary form of product, Preliminary field testing, and Revising main product. The data collection instrument was carried out by interviews, student needs questionnaires, material expert validation questionnaires, and media expert validation questionnaires which were then analyzed using a likert scale. The research data were analyzed using descriptive qualitative and quantitative descriptive methods. The results showed that the Ethno-STEM Based Plant Reproductive Organs Structure and Development Module obtained a score of 85 from the material validator in the moderately valid category and 84 from the media validator in the moderately valid category. Based on the validation results of material experts and media experts, the Ethno-STEM Based Plant Reproductive Organs Structure and Development Module can be said to be quite valid with small revisions, so that it can be used as a learning medium to help students master learning objectives after revisions are carried out.